Perbandingan Latihan Skipping dan Squad Jump Terhadap Power Otot Tungkai Pada Atlet Club Bola Voli Mitra Utama - Nabila Ika Pratiwi; Akhmad Sobarna; Sumbara Hambali (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to examine the effects of skipping and squat jump exercises and to compare their effects on lower limb power among athletes of the Mitra Utama Volleyball Club. This study employed an experimental method using a two group pretest–posttest design. The sample consisted of 20 athletes divided into two groups, each receiving skipping or squat jump training for 12 sessions. Lower limb power was measured using a vertical jump test. Data were analyzed using the Liliefors normality test, homogeneity test, and t-test at a significance level of 0.005. The results showed that both skipping and squat jump exercises significantly improved lower limb power. However, no significant difference was found between the two training methods. It can be concluded that skipping and squat jump exercises have relatively equal effectiveness in enhancing lower limb power in volleyball athletes. Keywords: Volleyball, Lower Limb Power, Skipping, Squat Jump.